Comfort Always: The Importance of Providing Psychological Support to Neurology Staff, Patients, and Families During COVID-19 - Foley, Jennifer A.; Chan, Edgar; van Harskamp, Natasja; Cipolotti, Lisa (Frontiers in Psychology, 2020)
Background: Although the impact of COVID-19 disruption on healthcare staff is increasingly understood, there has been no discussion of how it affects neurological patients and their families. Method: The Department of Neuropsychology at the National Hospital for Neurology and Neurosurgery established three new support services for staff, patients and families. Semi-structured interviews elicited concerns and if these were affected by COVID-19. Staff members were asked to complete the General Health Questionnaire-12. Results: Few staff members presented for support, but nearly all indicated significant distress, reflecting increased anxiety and reduced social support. Patients described exacerbated emotional, cognitive and physical concerns, and greater vulnerability to isolation and economic hardship. Families and carers reported increased distress arising from hospital lockdown. Conclusions: COVID-19 disruption affects staff, patients and families. Patients and families described additional challenges, which emphasise the importance of providing psychological support during these extraordinary times.